Design Principles of Single Atoms on Carbons for Lithium–Sulfur Batteries. Issue 10 (17th June 2020) - Fang, Lingzhe; Feng, Zhange; Cheng, Lei; Winans, Randall E.; Li, Tao
Abstract: The study of lithium–sulfur (Li‐S) batteries has generated various rationally designed cathodes and modified separators. However, the shuttle of soluble lithium polysulfides (LiPSs) and the sluggish kinetics of transformation of LiPSs to Li2 S2 /Li2 S still hinder the achievement of long‐life cycling and high‐rate of Li‐S batteries. Even though several kinds of nanocatalysts have been studied, the catalytic effects for Li‐S batteries are not ideal. Single atoms (SAs) with high surface free energy are found to serve as both anchoring and electrocatalytic centers for LiPSs. Atomically dispersed metal catalysts on carbon provide conductive and flexible hosts for dielectric sulfur. Moreover, SAs as the uniform lithiophilic sites can reduce the nucleation overpotential and ensure uniform plating of Li. In this review, the latest strategies for preparation of SAs supported on carbons are provided for the application of Li‐S batteries, including cathodes, modified separators, and Li metal anodes. In addition, it also discusses how SAs with high catalytic activity can help build better Li‐S batteries and the design principles for SAs. Finally, the future directions of SAs in energy storage applications are proposed. Abstract : Single atoms supported on carbons through metal–nonmetal bonds can catalyze polysulfide intermediate conversion reactions, especially the sluggish redox reaction between Li2 S2 and Li2 S. Strong polysulfide adsorption ability and high surface free energy also make single atoms ideal anchoring centers for soluble polysulfides and nucleation sites for Li plating.